The effect of nitric oxide supplement intake on neutrophils, Lymphocytes, and NLR of health workers exposed to Covid-19 in Indonesia - Tualeka, Abdul Rohim; Widajati, Noeroel; Dwi Winarno, Didik; Jalaludin, Juliana; Huda, Nuh; S Russeng, Syamsiar; Ahsan, Ahsan; Susilowati, Indri H.; Rahmawati, Pudji; Ratnaningsih, Titin (PalArch Foundation, 2021)
Objective: The COVID-19 pandemic has hit around 139 countries in the world. This virus can reduce immunity in humans and failure to control it can result in death. The purpose of this study was to determine the effect of NO supplementation on neutrophil, lymphocyte, and NLR values. Method: The research design used pre-experimental with one group pre-post test, the total sample was 80 health workers who were exposed to COVID-19, the independent variable was the provision of NO and the dependent variable was the result of a hematological examination (lymphocytes, neutrophils, and NLR). The intervention was given NO 500 mg mixed with warm water 250 ccs, given 3 times a day for 5 days, data analysis used the T-test with a significance value of a<0.05. Results: There is a difference in the results of the pre and post-test hematology giving NO to the results of the examination of lymphocytes a=0.000, neutrophils a=0.000, and NLR a=0.000. Conclusion: Giving NO to health workers exposed to COVID-19 can normalize the neutrophil, lymphocyte, and NLR values and the immune system to fight the coronavirus.